A protein corona sensor array detects breast and prostate cancers - Digiacomo, Luca; Jafari-Khouzani, Kourosh; Palchetti, Sara; Pozzi, Daniela; Capriotti, Anna Laura; Laganà, Aldo; Zenezini Chiozzi, Riccardo; Caputo, Damiano; Cascone, Chiara; Coppola, Roberto; Flammia, Gerardo; Altomare, Vittorio; et al. (Nanoscale, 2020)
Following exposure to human plasma (HP), nanoparticles (NPs) are coated with a biomolecular layer referred to as a protein corona. We recently revealed that characterizing the protein coronas of various NPs may provide a unique opportunity for cancer identification and discrimination. In other words, protein corona profiles of several NPs, when being analyzed using classifiers, would provide a unique "fingerprint" for each type of disease. Here, we probed the capacity of the protein corona for the identification and discrimination of breast and prostate cancer patients from healthy individuals. Using three lipid NP formulations with distinct physical-chemical properties as a cross-reactive sensor array and a supervised random forest classifier, we identified a set of proteins that showed a significant difference in cancer patients and control subjects. Our data show that many of the corona proteins with the highest discrimination ability between oncological patients and healthy individuals are related to cellular and molecular aspects of breast and prostate cancers.